A Method for Recognizing Entities in Power News Texts Based on Dependency Syntactic Parsing - Wu, Yun; Liu, Xinru; Du, Yan; Yang, Jieming; Liu, Zhenhong; Yang, Kai; Wang, Ziyi (Journal of advanced computational intelligence and intelligent informatics, 2025)
Addressing the challenge that news texts in the power field often contain numerous professional terms and many new terms are generated every year, which are difficult to accurately identify using general named entity recognition methods, this paper proposes an entity recognition model for power texts based on dependency syntactic analysis (SYN-BiLSTM-CRF). This model first generates power text word vectors and inputs them into a forward LSTM for feature extraction. Simultaneously, dependency syntactic parsing is performed on the power text, and the syntactic information vectors are fused with the output of the forward LSTM before being input into a backward LSTM. This enhances the model’s ability to learn inter-word dependency relations by incorporating additional syntactic features. Finally, CRF is employed to obtain the predicted NER labels. The experiments demonstrate that the proposed SYN-BiLSTM-CRF model achieves an F1-score of 85.36% on power-related texts, representing a 2.78% improvement over the baseline BiLSTM-CRF model (82.58%). Additionally, it attains a recall of 89.06%, outperforming the BERT model’s recall (87.59%). These results prove that the proposed method significantly enhances entity recognition accuracy in this specialized domain.